Innovating in a secret world : the future of national security and global leadership - Srivastava, Tina P. (Potomac Books, an imprint of the University of Nebraska Press, 2019)
"Our national security increasingly depends on access to the most sophisticated and advanced technology. Yet the next time we set out to capture a terrorist leader, we may fail. Why? The answer lies in a conflict between two worlds. One is the dynamic, global, commercial world with its thriving innovations. The other is the world of national security, in which innovation is a matter of life or death. The conflict is about secrecy. Innovating in a Secret World is a detailed examination of the U.S. government and innovation landscapes and of the current trends in often secret national security-related research and development (R & D). Based on case studies, detailed research, and interviews with executives at Fortune 500s, startup entrepreneurs, and military directors and program managers, this accessible and timely book is a must-read. Tina P. Srivastava evaluates whether the strategy of technology innovation in the world of national security unintentionally leaves certain innovations behind or unintentionally precludes certain classes of innovators from participating. She identifies the unintended consequences and emergent behaviors of this conflict. This examination unfolds in a complex, dynamic system that includes the legal framework in which technology innovation must exist. For more than a decade Srivastava has been on the front lines of cutting-edge technology innovation. She suggests focusing on an emerging class of R & D strategy called "open innovation"--A strategy that broadens participation in innovation beyond an individual organization or division traditionally assigned to perform R & D activities. Through compelling stories of commercial and early government applications, she shows how open technology innovation strategies can enable, accelerate, and enhance technology innovation. Successful incorporation of open innovation into the previously closed U.S. government R & D landscape can yield profound benefits to both national security and global leadership."--